Changes in home care clients' characteristics and home care in five European countries from 2001 to 2014: comparison based on InterRAI - Home Care data - I. V. Kristinsdottir; P. V. Jonsson; I. Hjaltadottir; K. Bjornsdottir (BMC, 2021)
Abstract Background Policymakers advocate extended residence in private homes as people age, rather than relocation to long-term care facilities. Consequently, it is expected that older people living in their own homes will be frailer and have more complex health problems over time. Therefore, community care for aging people is becoming increasingly important to facilitate prevention of decline in physical and cognitive abilities and unnecessary hospital admission and transfer to a nursing home. The aim of this study was to examine changes in the characteristic of home care clients and home care provided in five European countries between 2001 and 2014 and to explore whether home care clients who are most in need of care receive the care required. Methods This descriptive study used data from two European research projects, Aged in Home Care (AdHOC; 2001-2002) and Identifying best practices for care-dependent elderly by Benchmarking Costs and outcomes of Community Care (IBenC; 2014-2016). In both projects, the InterRAI-Home Care assessment tool was used to assess a random sample of home care clients 65 years and older in five European countries. These data facilitate a comparison of physical and cognitive health and the provided home care between countries and study periods. Results In most participating countries, both cognitive (measured on the Cognitive Performance Scale) and functional ability (measured on the Activities of Daily Living Hierarchy scale) of home care clients deteriorated over a 10-year period. Home care provided increased between the studies. Home care clients who scored high on the physical and cognitive scales also received home care for a significantly higher duration than those who scored low. Conclusion Older people in several European countries remain living in their own homes despite deteriorating physical and cognitive skills. Home care services to this group have increased. This indicates that the government policy of long-term residence at own home among older people, even in increased frailty, has been realised.